Sexuality in Adults with Differences/Disorders of Sex Development (DSD): Findings from the dsd-LIFE Study. Issue 8 (17th November 2019) - Kreukels, Baudewijntje P. C.; Cohen-Kettenis, Peggy T.; Roehle, Robert; van de Grift, Tim C.; Slowikowska-Hilczer, Jolanta; Claahsen-van der Grinten, Hedi; Lindén Hirschberg, Angelica; de Vries, Annelou L. C.; Reisch, Nicole; Bouvattier, Claire; Nordenström, Anna; Thyen, Ute; et al.
Abstract: For various reasons, sexuality of individuals with differences/disorders of sex development (DSD) may be affected. The aim of the study was to describe sexual activity, satisfaction with sex life, satisfaction with genital function, and sexual problems in people with different DSD conditions. Data were collected from 1, 040 participants in Europe. Many people with a variety of DSD conditions do not appear to be satisfied with their sex life, experience a variety of sexual problems, and are less sexually active than the general population; therefore sexuality should be explicitly addressed in the care of people with DSD.